PEMAHAMAN KONSEP MATEMATIKA DITINJAU DARI MODEL PEMBELAJARAN KOOPERATIF PADA SMP NEGERI DI KECAMATAN TARUMAJAYA BEKASI - Syafa’atun, Syafa’atun (Jurnal Cakrawala Ilmiah, 2024)
The influence of the cooperative learning model on understanding mathematics concepts of State Middle School students in Tarumajaya subdistrict. This type of research is quantitative research with the method used in this research is Quasi Experimental Treatment By Level, namely by providing different types of treatment to two student learning groups. There is a significant influence of the cooperative learning model on the understanding of mathematics concepts of State Middle School students in Tarumajaya Bekasi sub-district. This is proven by the Sig value. 0.000 < 0.05 and Fcount = 22.306. Thus, there is a significant difference in the influence of the cooperative learning model on students' understanding of mathematical concepts. This is supported by the average score for understanding mathematical concepts using the jigsaw cooperative learning model of 80.83, which is higher than understanding mathematical concepts using the TPS cooperative learning model of 71.27.